Identification of patients at higher risk for myocardial injury following elective coronary artery intervention - Abu Sharar, Haitham; Helfert, Stefanie; Vafaie, Mehrshad; Pleger, Sven Torsten; Chorianopoulos, Emmanuel; Bekeredjian, Raffi; Katus, Hugo; Giannitsis, Evangelos (Catheterization and cardiovascular interventions, 2020)
Objectives - To evaluate myocardial injury and infarction (MI) following elective percutaneous coronary intervention (PCI). - - Background - The substantially higher analytical power of high‐sensitivity troponin (hsTn) assays allows detection of minor cardiac troponin (cTn) levels, which may be useful in monitoring myocardial injury and guiding therapies.